The Association of Hypoglycemia Assessed by Continuous Glucose Monitoring With Cardiovascular Outcomes and Mortality in Patients With Type 2 Diabetes - Wei, Wei; Zhao, Shi; Fu, Sha-li; Yi, Lan; Mao, Hong; Tan, Qin; Xu, Pan; Yang, Guo-liang (Frontiers in Endocrinology, 2019)
Objective: Hypoglycemia has been shown to promote inflammation, a common pathogenic process in many chronic health conditions including diabetes and cardiovascular disease. The aim of this study was to investigate the association of hypoglycemia assessed by continuous glucose monitoring (CGM) with major adverse cardiovascular event (MACE) outcomes and all-cause mortality. Methods: A retrospective cohort study was conducted with 1520 patients with type 2 diabetes mellitus (T2DM). The severity of hypoglycemia event was assessed by CGM system. Results: Three hundred and forty-seven participants experienced hypoglycemia events (323 with mild hypoglycemia and 24 with severe hypoglycemia). A fraction of 72.62% hypoglycemia was asymptomatic. During a median follow-up of 31 months, 380 participants reached the primary outcome of MACE (61 cardiovascular death, 50 non-fatal myocardial infarction [MI], 116 non-fatal stroke, 153 unstable angina requiring hospitalization), 80 participants died before the end of the study. In multivariate Cox regression models, hypoglycemia was associated with cardiovascular death (HR 2.642[95CI% 1.398- 4.994]), non-fatal stroke (HR 1.813 [95CI% 1.110-2.960]) and all-cause mortality (HR 1.960 [95 CI% 1.124- 3.418]) after the full adjustment. Hypoglycemia was not associated with non-fatal MI and unstable angina. The HR of severe hypoglycemia was higher than mild hypoglycemia for cardiovascular death. Patients with symptomatic and asymptomatic hypoglycemia had similarly MACE outcomes and all-cause mortality. Conclusions: CGM is effective to detect asymptomatic and nocturnal hypoglycemia. Hypoglycemia is associated with an increased risk of non-fatal stroke, cardiovascular related death and total mortality. The cardiovascular mortality is dose-dependent on the severity of hypoglycemia.